Clinical Pharmacist’s Intervention to Improve Medication Titration for Heart Failure: First Experience from Sudan - Ahmed KO; Taj Eldin I; Yousif M; Albarraq AA; Yousef BA; Ahmed N; Babiker A (Integrated Pharmacy Research and Practice, 2021)
Kannan O Ahmed,1 Imad Taj Eldin,2 Mirghani Yousif,1 Ahmed A Albarraq,3 Bashir A Yousef,4 Nasrein Ahmed,5 Anas Babiker6 1Department of Clinical Pharmacy, Faculty of Pharmacy, University of Gezira, Wad Medani, Sudan; 2Department of Pharmacology, Faculty of Pharmacy, University of Gezira, Wad Medani, Sudan; 3Pharmacy Practice Research Unit, Department of Clinical Pharmacy, College of Pharmacy, Jazan University, Jazan, Saudi Arabia; 4Department of Pharmacology, Faculty of Pharmacy, University of Khartoum, Khartoum, Sudan; 5Department of Cardiology, Ahmed Gasim Cardiac Surgery and Renal Transplantation Centre, Khartoum, Sudan; 6Department of Cardiology, Royal Care International Hospital, Khartoum, SudanCorrespondence: Kannan O AhmedDepartment of Clinical Pharmacy, Faculty of Pharmacy, University of Gezira, Hospital Street No. 1, Wad Medani, 21112, SudanTel +249 121860001Fax +249 511861180Email omerkannan@gmail.comBackground: Medications known to improve outcomes in heart failure (HF) are either not prescribed or prescribed at sub-therapeutic doses. The addition of clinical pharmacists to the HF team positively impacts optimizing prognostic medications for a patient with HF with reduced ejection fraction (HFrEF).Objective: To assess the intervention of the clinical pharmacist as part of the multidisciplinary (MD) team in up-titration to achieve target doses of key therapeutic agents for HFrEF.Methods: This was a prospective one group pretest-posttest interventional study; a comparison of the target dose achievement of key therapeutic agents for HFrEF was performed before and after clinical pharmacist interventions.Results: Out of 110 HFrEF patients, 57.3% were males, and the mean age of patients was 55.8 years (SD 12.6). Cardiomyopathy was the leading cause of HF. At baseline, 86% were on angiotensin-converting enzyme inhibitors/angiotensin receptor blockers/angiotensin receptor-neprilysin inhibitors (ACEIs/ARBs/ARNi) and 93.6% on beta blockers (BBs). At the end of study, the proportion of patients achieved the target dose was significantly increased (0 vs 77.4%, 6.8 vs 85.4%, and 0 vs 55.6%) for ACEIs, ARBs and ARNi, respectively, and (8.6% vs 66.1%; P = 0.001) for BBs. Moreover, the up-titration process was associated with significant improvement in most clinical as ejection fraction and New York Heart Association (NYHA) scale and laboratory characteristics.Conclusion: As a part of the MD team in the outpatient HF clinic, the clinical pharmacists increased the percentage of HFrEF patients achieving the target or maximal doses of key therapeutic agents and improving clinical and laboratory parameters.Keywords: clinical pharmacist, intervention, heart failure, medications titration, Sudan